Alteration in vaccination rates and an evaluation of physicians’ perceptions of the possible impact of the SARS-CoV-2 pandemic on childhood vaccinations in Ankara, Turkey - Ateş Kara; Sare İlbay; Osman Topaç; Elif Ayla Arabulan; Hasan Tezer; Nilüfer Tavukçu; Çiğdem Şimşek (Human Vaccines & Immunotherapeutics, 2021)
Vaccination is the most effective and cost-efficient approach to protect both individual and community health. Decreased vaccination rates have been reported in many countries during the COVID-19 pandemic. In this study, we compared the vaccination rates of the current year with those of the same period of 2019 in Ankara and presented the physicians’ thoughts about effects of COVID-19 pandemic on vaccinations in Turkey. An online survey was sent to family practitioners, pediatricians, and pediatric infectious disease specialists to ascertain their thoughts on vaccination during the pandemic. A majority of family practitioners stated that, despite hesitations, families brought their children for vaccination. They noted that vaccination should be emphasized, physicians should be supported by health authorities, and all related media and social media channels should be used to promote maintaining vaccinations. In contrast, pediatricians and pediatric infectious disease specialists were of the opinion that families were expressing greater hesitation and would not bring their children for vaccination. Vaccination rates in Ankara have decreased 2–5% during the pandemic, and the greatest decrease was observed for vaccines administered after 18 months of age. Outbreaks of vaccine-preventable diseases can threaten community health worldwide. Thus, vaccinations must continue, and effective regulations and recommendations need to be implemented by healthcare authorities to promote it.